Systematic review and meta-analysis on the prevalence and risk factors of oral frailty among older adults - Pingping Huang; Linjing Wu; Rongxiang Zhang; Rongxiang Zhang; Shiqi Chen; Shiqi Chen; Yu Zhang; Yuan Chen; Yuan Chen (Frontiers in Medicine)
ObjectivesThe present study aim to systematically review the prevalence and influencing factors of oral frailty in older people.MethodsA search strategy was developed and implemented to systematically review literature across PubMed, Embase, Web of Science, MEDLINE (via EBSCOhost), CINAHL, the Cochrane Library, Scopus, China Knowledge Resource Integrated Database (CNKI), Wanfang Data, Chinese Biomedical Database (CBM), and Weipu Database (VIP), in accordance with the PRISMA 2020 guidelines. Our search encompassed studies published up to June 28, 2024, that investigated the prevalence or risk factors of oral frailty among older adults. Literature screening, data extraction, and quality assessment were independently performed by two researchers, followed by data analysis using Stata 17 software. This study has been registered with PROSPERO.ResultsA total of 35 studies involving 202,864 participants were analyzed. The overall prevalence of oral frailty among older adults was 34.0% (95% CI: 27.9–40.1%, I2 = 99.7%, p < 0.001). Subgroup analyses revealed statistically significant differences in the prevalence of oral frailty among different assessment tools and age groups (p < 0.05). Univariate meta-regression analysis indicated that the age was related to heterogeneity in the study (p < 0.05). Factors such as age, gender, physical frailty, pre-frailty, and unattached were identified as key risk factors for oral frailty in older adults (all p < 0.05).ConclusionThe incidence of oral frailty among older adults is notably high and influenced by a variety of factors. Healthcare professionals are encouraged to actively implement preventive and treatment measures addressing the controllable factors associated with oral frailty. Such proactive efforts are essential for early identification of high-risk individuals, which can help reduce the prevalence of oral frailty among older adults and enhance their quality of life.Systematic Review RegistrationPROSPERO (CRD42023488653: https://www.crd.york.ac.uk/prospero/).